Perfilman Nasional dalam Negara Orde Baru - Aulia, Masyitoh; Kurniawati, Asti (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
The development of national films during the New Order era experienced ups and downs. This condition is influenced by various factors, including competition with imported films, funding problems, the presence of private television stations, and so on. However, among the various influencing factors, state policy holds the main determining key. This article explains the dynamics of national cinema in the New Order country which experienced development in the 1970s and 1980s and experienced decline in the 1990s. The sources used to prepare this article are archives, contemporary newspaper reports, and oral sources.